Famous students of the “Nizamiya” madrasas - Narzullayeva, Zulxumor (The Lingua Spectrum, 2025)
This article discusses the prominent scholars educated at the “Nizamiya” madrasas who made a significant contribution to the development of world science and culture. During the reign of the Seljuk rulers, the territories under their control witnessed a remarkable flourishing of scientific and intellectual life, as evidenced by the activities of many great thinkers of that era. One of the key factors behind this progress was the educational reforms carried out by the renowned vizier Nizam al-Mulk and the Seljuk dynasty. The traditional respect and commitment to knowledge and education reached its peak during the Seljuk period, marking a pivotal stage in the history of Islamic scholarship.